Guided imagery and physiologic responses of selected hospitalized hypertensive patients - Dela Cruz, Remigio G. Jr
Current treatment modalities have thus so far been limited in managing the steady rise in the number of hypertension and hypertension-related deaths in the Philippines. Several factors can be attributed to this limitation. Still the need to control hypertension cannot be overemphasized since it has been shown to be a major risk factor in the development of certain cardiovascular diseases such as stroke, coronary artery disease, and heart failure. Attempts have been made by clinicians and researchers to find alternative therapies that would be used either alone or in combination with existing antihypertensive medications to improve the health and wellbeing of hypertensive patients. One group that is currently being investigated for its potential benefits is Biobehavioral Interventions.